Marriage Traditions and Family Resilience in Bugis Bone Society: A Study of Islamic Law and Islamic Education - Said, Wardana; Hukmiah, Hukmiah; Nur, Suriani; Wahyuni, Sri; Akbar, Rahmatul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Indonesia, with the highest Muslim population globally, has experienced significant changes in its legal landscape throughout history. These changes have resulted in the coexistence of various legal systems, including the Islamic law, the customary law, and the state law. The three variations of societal practices, including marriage, persist to be the topic of academic discussion. Marriage has both legal and customary aspects, as well as philosophical and educational components. This study is an empirical sociological investigation that specifically examines the marriage tradition within the Bugis society, employing the theoretical framework of the Islamic law and Islamic education. The data collection approaches employed include interviews, observations, and document analysis. This study finds that the marriage process, both before and after implementation, is conducted with wisdom and is imbued with profound values within the family and the community involved in the marriage. The relationship between marriage traditions and family resilience is rooted in the ideals and meanings of Islamic legal philosophy. The marriage rituals, from preparation to implementation and beyond, serve to build and bind bonds between families. The marriage tradition within the Bugis Bone group encompasses educational principles, including aqidah education, moral education, and social education. The educational ideals serve as the bedrock for enhancing the resilience of families in the Bugis Bone community.